Recurrent takotsubo syndrome with worsening of left ventricular outflow obstruction during haemodialysis: a case report. Issue 2 (21st February 2020) - Takada, Takuma; Jujo, Kentaro; Ishida, Issei; Hagiwara, Nobuhisa
Abstract: Background: The recurrence rate of takotsubo syndrome (TS) has been reported as 1.8% per patient-year while left ventricular outflow tract (LVOT) obstruction is comorbid in 10–25% of all instances of TS. The clinical course of recurrent TS with associated LVOT while on haemodialysis has rarely been reported. Case summary: This case report involves a 60-year-old female patient receiving regular haemodialysis who was admitted for chest pain during ballroom dancing. Four years prior, she had suffered TS, and fully recovered after the hospitalization. An emergent coronary angiogram done during the second hospitalization showed no significant stenosis, and left ventriculography demonstrated mid-apical akinesia and basal hyperkinesia. Based on these findings, we diagnosed the recurrence of TS. Later in the admission, chest pain reappeared with the start of haemodialysis. A transthoracic echocardiogram demonstrated mean pressure gradient (PG) of LVOT was 58 mmHg, with systolic anterior motion of the mitral valve and basal-wall hyperkinesia. The main aetiology for her symptoms was considered as an exacerbation of LVOT obstruction due to removing intravascular volume by haemodialysis. After starting landiolol at 3 μg/kg/min, PG of LVOT and symptoms gradually improved with uptitration of landiolol. Finally, her chest pain resolved when mean PG of LVOT was down to 38 mmHg using 10 μg/kg/min of landiolol. Discussion: To our knowledge, this is the first report of a recurrent TS case comorbid with LVOT obstruction while on regular haemodialysis. Landiolol, the ultrashort-acting beta-blocker, may be a promising therapeutic option for rapid recovery of increased PG due to LVOT obstruction.